Experiments to confront the environmental extremes of climate change. Issue 4 (1st May 2015) - Kayler, Zachary E; De Boeck, Hans J; Fatichi, Simone; Grünzweig, José M; Merbold, Lutz; Beier, Claus; McDowell, Nathan; Dukes, Jeffrey S
Abstract : Extreme climate conditions can dramatically alter ecosystems and are expected to become more common in the future; however, our understanding of species and ecosystem responses to extreme conditions is limited. We must meet this challenge by designing experiments that cover broad ranges of environmental stress, extending to levels well beyond those observed currently. Such experiments are important because they can identify physiological, community, and biogeochemical thresholds, and improve our understanding of mechanistic ecological responses to climate extremes. Although natural environmental gradients can be used to observe a range of ecological responses, manipulation experiments – including those that impose drought and heat gradients – are necessary to induce variation beyond common limits. Importantly, manipulation experiments allow for determination of the cause and effect of species and ecosystem threshold responses. We present a rationale and recommendations for conducting extreme experiments that extend beyond the historical and even the predicted ranges of environmental conditions.